PENGARUH KONTEN VIDEO PENDEK BERBASIS AI DAN PENGALAMAN PELANGGAN TERHADAP NIAT MENONTON ULANG: PERAN MEDIATOR KEPUASAN PELANGGAN PADA GEN Z - Abdul Hadi; Gadhing Dwi Nugrahanto (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
Abstract This study examines the influence of Artificial Intelligence (AI) based short video content and customer experience on rewatch intention, with customer satisfaction serving as a mediating variable, among Generation Z in Klaten Regency. The purpose of this research is to identify the relationships between these variables and to explore the role of customer satisfaction in strengthening rewatch intention. A quantitative approach with a survey design was employed, involving 165 Gen Z respondents in Klaten Regency selected through random sampling techniques. The data were analyzed using Structural Equation Modeling (SEM) to test the relationships among the studied variables. The results indicate that AI-based short video content and customer experience have a significant positive effect on customer satisfaction, which in turn influences rewatch intention. Furthermore, AI-based short video content was also found to have a direct effect on rewatch intention. The study contributes theoretically by enriching the understanding of the influence of AI and customer experience in the context of digital marketing and provides practical implications for marketers in designing more relevant and satisfying user experiences. These findings also offer valuable insights for platform developers to enhance user loyalty through personalized technology.